Regulation of miRNAs Expression by Mutant p53 Gain of Function in Cancer - Madrigal, Tzitzijanik; Hernández-Monge, Jesús; Herrera, Luis A; González-De la Rosa, Claudia Haydée; Domínguez-Gómez, Guadalupe; Candelaria, Myrna; Luna-Maldonado, Fernando; Calderón González, Karla G; Díaz-Chávez, José (Frontiers in Cell and Developmental Biology, 2021)
The p53 roles have been largely described; among them, cell proliferation and apoptosis control are some of the best studied and understood. Interestingly, the mutations on the 6 hotspot sites within the region that encodes the DNA-binding domain of p53 give rise to other very different variants. The particular behavior of these variants led to consider p53 mutants as separate oncogene entities; that is, they do not retain wild type functions but acquire new ones, namely Gain-of-function p53 mutants. Furthermore, recent studies have revealed how p53 mutants regulate gene expression and exert oncogenic effects by unbalancing specific microRNAs (miRNAs) levels that provoke epithelial-mesenchymal transition, chemoresistance, and cell survival, among others. In this review, we discuss recent evidence of the crosstalk between miRNAs and mutants of p53, as well as the consequent cellular processes dysregulated.